Moving policy implementation theory forward: A multiple streams/critical juncture approach. (October 2019) - Howlett, Michael
Meta-reviews of the implementation literature have constantly bemoaned a lack of theory in this area. This is partially a function of the policy sciences having inherited a tradition of descriptive work in public administration, a historical phenomenon exacerbated by the more recent addition to this corpus of an equally atheoretical set of works in public management. As a result, the study of policy implementation within the policy sciences remains fractured and largely anecdotal, with a set of proto-theories competing for attention – from network management to principal–agent theory, game theory and others – while very loose frameworks like the 'bottom-up vs. top-down' debate continue to attract attention, but with little progress to show for more than 30 years of work on this subject. This article argues the way out of this conundrum is to revisit the subject and object of policy implementation through the lens of policy process theory, rather than appropriating somewhat ill-fitting concepts from other disciplines to this area of fields of study. In particular, it looks at the recent synthesis of several competing frameworks in the policy sciences – advocacy coalition, multiple streams and policy cycle models – developed by Howlett, McConnell and Perl and argues this approach, hitherto applied only to the 'front end' activities of agenda setting and policy formulation, helps better situate implementation activities in public policy studies, drawing attention to the different streams of actors and events active at this phase of public policy-making and helping to pull implementation studies back into the policy science mainstream.